Perioperative Weakness: Clinical Vignette and Review of Mechanism, Incidence, and Risk Factors. (October 2020) - Ruiz-Peters, Michael; Winston, Paul; Krauss, Emily M.
Abstract : Supplemental digital content is available in the text.